What Does the Future Hold for the International Banking System? - Dailami, Mansoor; Adams-Kane, Jonathon (World Bank, Washington, DC, 2014)
The international banking industry faces a challenging future, having to consolidate at a time of heightened global financial volatility, anemic growth in advanced countries, and shifting global growth balances. After a long period of sustained expansion and accommodating regulatory treatment, the structure of international banking is changing as global banks' business strategies shift toward fast-growing emerging-market economies. The center of gravity for international lending is shifting, with the role of European banks shrinking and American, Japanese, and emerging-market banks filling in the space. Against this backdrop, the current debate on adding economic stimulus to support the sputtering global economic recovery should consider the possible contractionary impacts of bank deleveraging, even with global interest rates remaining at historically low levels.